The Other Side of the Bell Curve: Multivariate Base Rates of High Scores on the Delis-Kaplan Executive Function System. (15th April 2020) - Karr, Justin E.; Garcia-Barrera, Mauricio A.; Holdnack, James A.; Iverson, Grant L.
Abstract: Objective: Previous researchers have examined the frequency at which healthy participants obtain one or more low scores on neuropsychological test batteries, proposing five psychometric principles of multivariate base rates: (a) low scores are common, with their frequency contingent on (b) the low score cutoff used, (c) the number of tests administered/interpreted, and (d) the demographic characteristics and (e) intelligence of participants. The current study explored whether these principles applied to high scores as well, using the Delis-Kaplan Executive Function System (D-KEFS). Method: Multivariate base rates of high scores (≥75th, ≥84th, ≥91st, ≥95th, and ≥98th percentiles) were derived for a three-test, four-test, and full D-KEFS battery, using the adult portion of the normative sample (aged 16–89 years; N = 1050) stratified by education and intelligence. The full D-KEFS battery provides 16 total achievement scores (primary indicators of executive function). Results: High scores occurred commonly for all batteries. For the three-test battery, 24.1% and 12.4% had 1 or more scores ≥95th percentile and ≥98th percentile, respectively. High scores occurred more often for longer batteries: 61.6%, 72.9%, and 87.8% obtained 1 or more scores ≥84th percentile for the three-test, four-test, and full batteries, respectively. The frequency of high scores increased with more education and higher intelligence. Conclusions: The principles of multivariate base rates also applied to high D-KEFS scores: high scores were common and contingent on the cutoff used, number of tests administered/interpreted, and education/intelligence of examinees. Base rates of high scores may help clinicians identify true cognitive strengths and detect cognitive deficits in high functioning people.